The Tendency of Former Indonesian Migrant Workers to Earn a Living Wage When Returning to Work in Indonesia: A Case Study of Malaysia's Destination Country - Sucihatiningsih Dian Wisika Prajanti; Nana Kariada Tri Martuti; R Benny Riyanto (Jurnal Penelitian Pendidikan, 2024)
While the experience of working abroad can provide new skills and knowledge, former migrant workers often face challenges in reintegrating into the local labor market upon returning to Indonesia. Malaysian migrant workers have a tendency to work for less than the minimum wage after returning to Indonesia. Using the August 2021 sakernas data and logit analysis, this study will discuss the probability of former Indonesian migrant workers with a destination country of Malaysia, to earn wages above or equal to the minimum wage in the place where they work. The results of the logit analysis show that former Indonesian migrant workers have a probability of earning a living wage upon returning to Indonesia. Those who have a greater probability are former migrant workers with male gender, have higher education and have a formal job after returning to Indonesia.